Gender Perspective and Women Drug Users: Specific Needs in Relation to Substance Use Treatments - Antonio Jesús Molina-Fernández; Jesús Saiz-Galdos; Irene María Arribas-Tiemblo; Gisela Hansen-Rodríguez; Iván Sánchez-Iglesias; Elena Ayllón-Alonso; Banesa Mena-García (Psychiatry International)
Women under treatment are a particular susceptibility group according to the classification of the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA). The average number of women under treatment is lower than men all across Europe, and the drop-out percentage is higher in women than men. The aim of this study was to investigate the factors associated with drug use problems among women under treatment. Methodology: Quantitative research. Data from 2179 people receiving recovery treatment were extracted from EuropASI surveys. The dependent variables in this study were (1) the patient’s family history of addiction and psychiatric disease, (2) the main substance consumed, (3) the lifelong and last month’s substance use, (4) the lifelong and last month’s emotional, physical and sexual abuse, and (5) the lifelong and last month’s psychiatric disorders (including suicide attempts). The factor was gender, taken as a dichotomous variable (male–female). Initially, the Kolmogorov–Smirnoff normality test and Levene’s test were used to understand whether the sample met the normality and homoscedasticity statistical assumptions. For quantitative variables, the Mann–Whitney U test was used. The confidence interval used was 95%. Results: Briefly, we found that women tend to consume more alcohol, use more medication, and suffer more depression, anxiety and suicidal ideation than men, both lifelong and in the last month. In addition, women suffer more abuses (emotional, physical, and sexual) than men, during their lifetime and in the last month. Conclusions: The data showed that women have specific needs and vulnerabilities that should be accounted for when providing treatment but are currently not. This situation evidences the need for specialized drug recovery programs for women, and not only that, programs must adapt to the needs of each woman’s particular situation. Moreover, it is pressing that a multifactorial approach is used in every intervention, given the multiplicity of factors influencing consumption and the evidence that fixed treatment programs are not satisfactorily intervening in the complex reality that surrounds people with addiction.